1996
DOI: 10.1086/192380
|View full text |Cite
|
Sign up to set email alerts
|

A Catalog of Recombination Lines from 100 GHz TO 10 Microns

Abstract: We have made accurate calculations of recombination lines of H, He, C, and S from 100 GHz to 10 km (30 THz) that are useful to radio astronomers working at high frequencies. In particular, the Ðne structure of hydrogen has been treated explicitly for the Ðrst time in this radio-astronomical context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 6 publications
2
32
0
Order By: Relevance
“…Towle et al [204] calculated the distributions of intensities of the fine-structure components of transitions between high members of hydrogen series in the local thermodynamic equilibrium (LTE) approximation. They showed that these distributions are highly asymmetric, and their shapes vary strongly depending on the difference between the principal quantum numbers Dn.…”
Section: The Concept Of Distinctive Energiesmentioning
confidence: 99%
“…Towle et al [204] calculated the distributions of intensities of the fine-structure components of transitions between high members of hydrogen series in the local thermodynamic equilibrium (LTE) approximation. They showed that these distributions are highly asymmetric, and their shapes vary strongly depending on the difference between the principal quantum numbers Dn.…”
Section: The Concept Of Distinctive Energiesmentioning
confidence: 99%
“…The intensities of small ∆n RRLs (i.e., Hnα transition) are higher than the intensities of larger ∆n RRLs (i.e., Hnβ, Hnγ, and Hnδ transitions) (Towle et al 1996). This explains the lower detection rates of ∆n > 1 RRLs for a given sensitivity.…”
Section: Detection Ratesmentioning
confidence: 96%
“…These k energies have a degeneracy gk,j=right2(2j+1)rightjk3/2right2j+1rightj=k1/2.The fine‐structure components typically span a frequency range of the order of MHz and thus cannot individually be resolved with ALMA due to their thermal broadening in the ionized gas, which can be much larger than their separation. However, the splitting can change the line profile, and the frequencies and Einstein coefficients must be computed using relativistic quantum mechanics (Towle et al ).…”
Section: Physics Of Hydrogen Recombination Linesmentioning
confidence: 99%
“…with M n = 0.190 775, 0.026 332, 0.008 1056, 0.003 4917, 0.001 8119, 0.001 0585 for n = 1, 2, 3, 4, 5, 6, respectively. The situation is more complicated for recombination lines in the ALMA bands because lines above 100 GHz show non-negligible fine-structure splitting (Towle, Feldman & Watson 1996). For each principal quantum number k, there are k different energies which depend on the total angular momentum j = 1/2, 3/2, .…”
Section: P H Y S I C S O F H Y D Ro G E N R E C O M B I Nat I O N L Imentioning
confidence: 99%
See 1 more Smart Citation